Florida's Property Tax Reform: Proposed Constitutional Changes - Rodney L. Clouser (EDIS, 2008)
FE705, a 6-page fact sheet by Rodney L. Clouser, is part of the Florida’s Property Tax Reform series. It discusses the four core components of the proposed constitutional amendment that will be voted on by Florida residences on January 29, 2008: exemption of tangible personal property, doubling the homestead tax exemption, portability of Save Our Homes differential statewide, and a ten percent cap on the increase in assessments of non-homestead property. Includes references. Published by the UF Department of Food and Resource Economics, December 2007.